Gender Equality and Property Rights in Family Relations - Reforming the Albanian Legislation - Aurela Anastasi (Academicus International Scientific Journal, 2025)

(untitled)
This paper seeks to examine various facets of gender-related property rights in Albania. It aims to elucidate implementation of the law can be distorted by erroneous mentalities and gender stereotypes, striving to find solutions to mitigate their impact. The purpose is to bring attention to shortcomings of laws, while contributing to the enforcement of legislation with a renewed focus on gender equality and fair family relations. The objective is to highlight the importance of law reforms and positive measures in eradicating misunderstandings during implementation of the laws. The methodology is predominantly grounded in the critical examination of legislation, considering historical and comparative perspectives, analyzing case law from courts, and observing institutional practices in Albania.